Teachers' Prophetic Leadership in Learning Aqidah Morals for Students at MA Al-Jufri Blumbungan Larangan - Fitriani R, Vina (Aksara Shofa, 2023)
Schools or educational institutions need a leader who has high integrity to develop a school or educational institution in line with the times. One of the leadership styles that can be applied in the library is prophetic leadership. This study aims to explain how Prophetic Leadership in Teacher Learning for Students at MA Al-Jufri Blumbungan Prohibitions in human resource management in a school or educational institution using the literature study method. Prophetic leadership is considered suitable and can be applied in a school or educational institution because a leader who has a prophetic leadership style has high integrity (As Sidq), can be trusted (Al Amanah) means the leader of a school or educational institution must prove a real form of work, At-Tabligh means that the leader of a school or educational institution must be willing to accept constructive input, and Al Fatanah, the leader of a school or educational institution must make himself able to work smartly and decisively by combining intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ). The leader of a quality school or educational institution will also produce quality human resources, therefore the role of the leader of a school or educational institution in managing human resources is very important to create professional and competent human resources in a school or educational institution.